Облікова політика, її суть та призначення - Букало, Надія Артемівна; Bukalo, Nadiia A. (Східноєвропейський національний університет імені Лесі Українки, 2015)
Статтю присвячено теоретичному обґрунтуванню та висвітленню окремих важливих елементів облікової політики, досліджено суть та призначення облікової політики. Визначено ряд чинників впливу на вибір і обґрунтування облікової політики. Досліджено, що важливою складовою загального механізму управління господарською діяльністю підприємств є уміло сформована облікова політика. Розглянуто причини та напрями, що зумовлюють формування облікової політики з врахуванням вимог чинного законодавства. The article is devoted to theoretical substantiation of certain critical accounting policies, investigated the nature and purpose of accounting policies. It is proved that the accounting policy is developed individually by each enterprise and is designed to ensure the reliability and accuracy of their financial information system. It is grounding a necessity in accounting policy in Ukraine. It is proved that an important part of the overall management mechanism and economic activity of enterprises is skillfully formed accounting policies. The causes and trends are reviewed that contribute to the formation of accounting policy with regard to the requirements of applicable law. Found that the purpose of accounting policy is to streamline your process to ensure complete, accurate and unbiased information for effective management. Enterprise independently develops accounting model that provides information about the company to all interested users.
Accointine policies its essence and purpose
Keywords: Облікова політика; бухгалтерський облік; фінансова звітність; принципи; accounting policies; accounting; financial reporting; principles